(untitled) (Global Journal of Human-Social Science, 2013)
Ecosystem services are the benefits that societies receive from the nature. These may be in the form of regulating, provisioning, supporting or cultural services. Wetland being one of the most productive ecosystems provides these services at no cost. These ecosystems also contribute to reducing disaster risk by serving as natural protective barriers or buffers and, thus, mitigating hazard impacts. But many such wetland ecosystems are tremendous stressed due to anthropogenic pressure. Wetlands on the fringes of river channels in the city are looked upon as a resource for different land use planning. The capital Delhi manifests all the ills that a river system (Yamuna) can possibly face, made the city more vulnerable and disaster prone as evident from frequent incidences of flood, water crisis and disease outbreak. Rapidly increasing urbanisation with limited integration of values and functions of flood plains in developmental planning has led to their fragmentation.